Impact of adjunctive cilostazol therapy on platelet function profiles in patients with and without diabetes mellitus on aspirin and clopidogrel therapy - Angiolillo, Dominick J.; Capranzano, Piera; Ferreiro, Jose Luis; Ueno, Masafumi; Capodanno, Davide; Dharmashankar, Kodlipet; Darlington, Andrew; Sumner, Sabrina; Desai, Bhaloo; Charlton, Ronald K.; Box, Lyndon C.; Zenni, Martin M.; Guzman, Luis A.; Bass, Theodore A. (Thrombosis and Haemostasis, 2011)
Cilostazol is a platelet inhibitor which when added to aspirin and clopidogrel has shown to reduce the risk of recurrent ischaemic events without an increase in bleeding. These clinical benefits have shown to be more pronounced in patients with diabetes mellitus (DM). However, it remains unknown whether cilostazol exerts different pharmacodynamic effects in patients with and without DM. This was a randomised, double-blind, placebo-controlled, cross-over pharmacodynamic study comparing platelet function in patients with and without DM on aspirin and clopidogrel therapy. Patients (n=111) were randomly assigned to either cilostazol 100 mg or placebo twice daily for 14 days and afterwards crossed-over treatment for another 14 days. Platelet function was performed at baseline, 14 days post-randomisation, and 14 days post-cross-over. Functional testing to assess P2Y12 signalling included flow cytometric analysis of phosphorylation status of vasodilatorstimulated phosphoprotein measured by P2Y12 reactivity index (PRI), light transmittance aggregometry and VerifyNow. Thrombin generation processes were also studied using thrombelastography. Significantly lower PRI values were observed following treatment with cilostazol compared with placebo both in DM and non-DM groups (p < 0.0001). The absolute between-treatment differences of PRI between groups was a 35.1% lower in patients with DM (p=0.039). Similar results were obtained using all other functional measures assessing P2Y12 signalling. Thrombin generation was not affected by cilostazol. Cilostazol reduces platelet reactivity both in patients with and without DM, although these pharmacodynamic effects are enhanced in patients with DM. Despite the marked platelet inhibition, cilostazol does not alter thrombin-mediated haemostatic processes, which may explain its ischaemic benefit without the increased risk of bleeding.
Keywords: Diabetes mellitus; coronary artery disease; platelets